Perceptual contents : a study on the nature of the contents of perceptual experience - Oinas, Simo (2013)
The aim of the thesis is to examine various views that have been advocated in contemporary discussions concerning the content of perceptual experiences. The nature of the contents posited in those views is the focus of this study. In the views that are discussed here, perceptual contents have been argued to be either conceptual, externalist, nonconceptual or particular. In this thesis, John McDowell is presented as the proponent of conceptual content, Jeff Speaks as the proponent of externalist content, Christopher Peacocke as the proponent of abstract nonconceptual contents, and Tim Crane as the proponent of particular nonconceptual content. The revised view of John McDowell, as well as the view of Charles Travis, is also briefly presented.